Links between depressive symptoms, self-esteem, socioeconomic status and parental rearing among adolescents - Malinauskienė, Oksana; Žukauskienė, Rita (Psichologija, 2004)
Theories of parent child interactions suggest that parent-child transactional styles substantially influence children’s acquisition of appropriate social interaction skills, as well as impacting related adjustment outcomes. Early childhood experiences have frequently been suggested as causal factors in the development of psychopathological manifestations in adolescence. In particular, dysfunctional rearing practices appeared to be highly correlated with different types of psychopathology or psychological problems developed later in life, such as depressive symptoms and low self-esteem. Nevertheless, despite an increasing number of studies, the results were rather inconsistent and as not providing valid information on the relationships between depressive symptoms, low self-esteem, socioeconomic status and parental rearing practices among adolescents. There is still a lack of information about the role of parental rearing and socioeconomic status of the family in the development of emotional problems and self-esteem in children and adolescents.The purpose of this cross-sectional study was to investigate possible relationships between depressive symptoms, self-esteem, socioeconomic status, parental rearing, gender and age. Convenient sample of adolescents (N = 300, from 16 to 18 years) was given a test measuring self-esteem, a test measuring depressive symptoms, and a test measuring parental rearing. The Lithuanian version of RSE (Rosenberg, 1965) has been used to assess self-esteem. The depression subscale of the Lithuanian version of YSR (Achenbach, 1991) has been used to assess depressive symptoms. Parental rearing (emotional warmth, rejection, overprotection) was assessed using the Lithuanian versijon of the EMBU (Arrindell, 1999; Arrindell et al., 1994). Three measures of socioeconomic status were used: mother’s education and father’s education, family income, and family structure (one or two parents).Depressive symptoms were found to be higher for girls than for boys, whereas self-esteem was found to be higher for boys than for girls. Depressive symptoms were associated with lower self-esteem, both for boys and girls. Multivariate regressional analysis indicated that depressive symptoms are significantly predicted by self-esteem for boys and girls, by parental rejection for boys and girls, and by parental overprotection only for girls. Depressive symptoms were not significantly predicted by any of the three socioeconomic status measures. In addition, self-esteem was significantly predicted by depression for boys and girls, by parental emotional warmth for boys and girls, and by parental overprotection and by familial income only for girls. The differences between the prediction of depressive symptoms and the prediction of self-esteem, which appeared negatively correlated, suggested etiological differences. The differences between gender, and the lower percent of explained variance by regression analysis for boys than for girls, suggested gender differences in etiology of depression and in etiology of self-esteem.
Keywords: depressive symptoms; self-esteem; socioeconomic status; parental rearing; adolescents